HIKMAH AL-TASYRI’ DALAM HUKUM POLIGAMI (Perspektif Filsafat Hukum Islam) - Fauza, Nilna (UIN Sunan Kalijaga Yogyakarta, 2012)
Poligamy is not new problem, but poligamy discourse is always being controversial issue in Indonesian community. In its tasyri‟ manner, poligamy is currently possible to be done based on certain reasons. But behind it‟s controversy in the society, there is community that disposed nash becoming dominant factor as faith strengthener while the reason is following Sunnah Rasul. But in a contrary, there is other community that refuses poligamy based on the argumentation of subordinative position of female community and discriminative policy for them. Historically, the practice of poligamy has been done before Islam era, even there was no limitation in marrying women. But since Islam has come, the practice of poligamy has been beginning to be restricted as four wives only, however it still becomes controversial issue in the society. So that, the writer efforts to investigate the philosophy of islamic law (falsafah al-tasyrī‟) about poligamy by exploring the philosophy value from its possibilities, wether it can realize the goal of marriage that is sakinah, mawaddah wa rahmah) or even bocomes a strict problem in the family. This article is one way to get bridge in taking attitude of its controvercial side in the society.